I pede fausto – psychology faculty! - Danyluk, I. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2018)
The article presents the history of the development, achievements and key developments of psychology department in National Taras Shevchenko University of Kyiv. The article describes important features of the faculty development and development of psychology in Ukraine in general. The article presents famous personalities that worked and had good scientific achievements at the faculty itself. It also covers the perspectives of psychology in Ukraine as well. It presents main manuscripts and published works of the faculty. What is more important, the article describes current ways of functioning and further strategic planning of the faculty. It describes how the faculty is going to achieve more and in what direction it will keep developing. It also should be noted that the faculty itself has significantly grown throughout its history and now became rather independent structure of the university.
Keywords: Department of Psychology; National Taras Shevchenko University of Kyiv; history of psychology; psychology in Ukraine